From First Lady to presidential candidate: masculinization in news coverage of female politicians - Alvarez Monsiváis, Edrei (Pontificia Universidad Católica de Chile, 2020)
The study presents cases of presidential candidates who were previously first ladies: Cristina Fernández (Argentina), Hillary Clinton (USA) and Margarita Zavala (Mexico). The objective was to register, in national newspapers (La Nación, Página/12, The Wall Street Journal, The New York Times, Reforma and La Jornada) which were the attributes of personality, thematic agenda and tone in the news emerged during both periods. Feminine (empathy, honesty, celebrity) and masculine (leadership, intelligence, toughness) personality traits were deductively established, as well as soft or feminine topics (culture, health, education) and hard or masculine topics (economy, security and corruption, foreign policy). We found a masculinization of the political personality and thematic agenda during the candidacy, not found significantly during their status as First Ladies. We detected that the tone of the news was negative when the female candidates were presented from a female personality and masculine topics. Among the conclusions we can highlight that women who run for presidential positions are forced to be more strategic in their political actions to be seen by citizens as capable of solving problems that are not culturally associated with femininity. The investigation concludes that the press placed the political woman in a paradox between being covered journalistically as women or as politicians, making them both eligible and ineligible for the presidency.